PENERAPAN METODE STORYTELLING UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS II DI SD NEGERI 1 SINGKOHOR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Kuswati; Nur Rohman (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2025)
This research aims to improve the understanding of grade II students of SD Negeri 1 Singkohor on the main message in Surah An-Nas through the application of the storytelling method. The problems faced are low student understanding due to conventional learning methods and lack of interest in learning. The research method used is classroom action research with two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects involved 35 grade II students of SD Negeri 1 Singkohor. Data was collected through written tests and observation of student learning activities. The results showed a significant increase in students' understanding of the material after the application of the storytelling method, with the percentage of completeness of learning outcomes increasing from 51.43% in pre-research to 77.14% in cycle I and 91.43% in cycle II. In addition, student learning activities also showed an increase from fair to good and excellent. The conclusion of this study is that the storytelling method is effective in increasing students' understanding and activeness in learning the main message material of Surah An-Nas in grade II elementary school.